2005
DOI: 10.1096/fj.04-2078rev
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G and immune tolerance in pregnancy

Abstract: Multiple mechanisms underlie the surprising willingness of mothers to tolerate genetically different fetal tissues during pregnancy. Chief among these is the choice of HLA-G, a gene with few alleles, rather than the highly polymorphic HLA-A and -B genes, for expression by the placental cells that interface directly with maternal blood and tissues. Novel aspects of this major histocompatibility complex class Ib gene include alternative splicing to permit production of membrane and soluble isoforms, deletions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
367
0
33

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(406 citation statements)
references
References 132 publications
6
367
0
33
Order By: Relevance
“…Moreover, FA-MSCs exhibit rare chromosomal changes, a stable karyotype, late senescence, and incapacity to generate teratomas that suggest their genetic stability (Shin et al 2009). In addition, these cells are poorly antigenic, expressing HLA-G for immune tolerance during pregnancy and thus are less likely to be rejected by transplant receivers (Hunt et al 2005). Therefore, they can be used in autologous as well as in allogenic transplantation.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%
“…Moreover, FA-MSCs exhibit rare chromosomal changes, a stable karyotype, late senescence, and incapacity to generate teratomas that suggest their genetic stability (Shin et al 2009). In addition, these cells are poorly antigenic, expressing HLA-G for immune tolerance during pregnancy and thus are less likely to be rejected by transplant receivers (Hunt et al 2005). Therefore, they can be used in autologous as well as in allogenic transplantation.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%
“…Its distinct expression pattern in very select placental trophoblast cells led the authors to raise the question of whether this molecule could provide new insight into the immune relationship between mother and fetus [32]. In the interim, it has been shown that HLA-G differs largely from other HLA class I molecules in that it is largely monomorphic and that very few differences exist between population groups [33][34][35]. The structural features of HLA-G have been determined to be quite complex in that five distinct forms exist, three membrane-anchored forms and two soluble forms.…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%
“…The structural features of HLA-G have been determined to be quite complex in that five distinct forms exist, three membrane-anchored forms and two soluble forms. While the expression of the fulllength HLA-G1 molecule seems to be restricted to invasive cytotrophoblast and thymic epithelium, the expression of the other variants, especially the soluble HLA-G5 variant, is more widespread, occurring throughout the placenta, chorionic membrane and decidua [34].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%
See 2 more Smart Citations